Clearance of platelet microparticles in vivo - Rank, Andreas; Nieuwland, R.; Crispin, A.; Grützner, S.; Iberer, M.; Toth, Bettina; Pihusch, R. (Platelets, 2011)
At present, little is known about the clearance of platelet-derived microparticles (PMP) in human blood, as due to ethical considerations infusion experiments with labeled microparticles are delicate. Therefore, we investigated the kinetics of PMP, which are abundantly present in apheresis platelet concentrates (PC), following platelet transfusion in severe thrombocytopenic patients (n = 11). PMP were double-stained with annexin V and cell-specific antibodies (anti-CD61, anti-CD63 or anti-CD62P, respectively) and detected by flow cytometry before and after transfusion of a single PC at fixed time intervals. Upon transfusion, the plasma levels of MP binding annexin V (2.5-fold), PMP (CD61+; 2.9-fold), and PMP from activated platelets (CD63+; 1.9-fold) or P-selectin (2.5-fold) increased immediately. The plasma levels of MP decreased with a half life of 5.8 hours (annexin V; 95% CI: 1.8-18.3) and 5.3 hours (CD61; 95% CI: 2.0-14.2). This is the first report in which the half life time of transfused PMP has been investigated in humans.